The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3906/sag-1908-70
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa horns; a new calvarial finding of mucopolysaccharidoses with well-known cranial MRI features

Abstract: Background/aim: Mucopolysaccharidoses (MPS) are a group of hereditary metabolic diseases. The aim of this study was to share the previously unreported calvarial finding of internal hypertrophy of the occipitomastoid sutures (IHOMS) together with some other wellknown cranial MRI findings in this patient series. Materials and methods:A retrospective evaluation was conducted of 80 cranial MRIs of patients who had been diagnosed and followed up with MPS from 2008 to 2019 in our center. Of these patients, 11 had Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Other cranial deformities were also noticed. Having analysed a complex group of MPS patients, they concluded that cranial pathologies might help in differentiating MPS types [ 33 ]. Similarly to Damar, IHOMS of varying expression degree were detected in all five of our children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cranial deformities were also noticed. Having analysed a complex group of MPS patients, they concluded that cranial pathologies might help in differentiating MPS types [ 33 ]. Similarly to Damar, IHOMS of varying expression degree were detected in all five of our children.…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged PVS are isointense to cerebrospinal fluid (CSF) and were reported within the white matter (WM), corpus callosum (CC), basal ganglia and brainstem. Among these, the involvement of CC appears to be the most distinctive upon comparison of MPS 1 patients and healthy controls [ 33 ]. A reduced CC volume had been reported among Hurler syndrome patients, standing out from attenuated phenotypes, and even more markedly from the healthy control group [ 34 ].…”
Section: Neuroimagingmentioning
confidence: 99%